Bone marrow-derived mesenchymal stem cells: A promising therapeutic option for the treatment of diabetic foot ulcers. (January 2023) - Dama, Ganesh; Du, Jiang; Zhu, Xinxing; Liu, Yanli; Lin, Juntang
Abstract: Chronic wounds fail to heal through the three normal stages of healing (inflammatory, proliferative, and remodelling), resulting in a chronic tissue injury that is not repaired within the average time limit. Patients suffering from type 1 and type 2 diabetes are prone to develop diabetic foot ulcers (DFUs), which commonly develop into chronic wounds that are non treatable with conventional therapies. DFU develops due to various risk factors, such as peripheral neuropathy, peripheral vascular disease, arterial insufficiency, foot deformities, trauma and impaired resistance to infection. DFUs have gradually become a major problem in the health care system worldwide. In this review, we not only focus on the pathogenesis of DFU but also comprehensively summarize the outcomes of preclinical and clinical studies thus far and the potential therapeutic mechanism of bone marrow-derived mesenchymal stem cells (BMSCs) for the treatment of DFU. Based on the published results, BMSC transplantation can contribute to wound healing through growth factor secretion, anti-inflammation, differentiation into tissue-specific cells, neovascularization, re-epithelialization and angiogenesis in DFUs. Moreover, clinical trials showed that BMSC treatment in patients with diabetic ulcers improved ulcer healing and the ankle-brachial index, ameliorated pain scores, and enhanced claudication walking distances with no reported complications. In conclusion, although BMSC transplantation exhibits promising therapeutic potential in DFU treatment, additional studies should be performed to confirm their efficacy and long-term safety in DFU patients.